THE ROLE OF GREEN IT ON ENHANCING ENERGY EFFICIENCY IN ORGANIZATIONS - Fajar Muttaqi; Nurul Badriah; Moh. Alfaujianto; Asep Surahmat (Scientific Journal of Information System, 2025)
Green IT is a cutting-edge information technology strategy designed to lessen the negative environmental effects of using IT infrastructure and devices. This study uses a qualitative methodology to investigate how Green IT is being adopted in different enterprises, emphasizing its advantages, difficulties, and practical implementation techniques. Document analysis and literature reviews from a range of sources pertaining to the adoption of green IT were used to gather data. According to the research, companies who use green IT see improvements in operational sustainability, lower carbon emissions, and increased energy efficiency. However, there are a number of significant obstacles to its adoption, including high upfront expenditures, ignorance, and reluctance to adopt new technologies. This report also emphasizes how crucial laws and rules are to encouraging the use of green IT. The study's conclusion highlights how putting Green IT into practice helps build a more sustainable and ecologically friendly technology ecosystem. As a result, companies must create all-encompassing plans for implementing Green IT, which should include purchasing energy-efficient equipment and increasing organizational understanding. This study helps policymakers, practitioners, and scholars better understand and support the future adoption of green IT.